Estrategias de aprendo en casa y el aprendizaje de personal social en los niños de cuatro años de la Institución Educativa Inicial N° 454 Mi Casita del Saber, Nauta 2022 - Pastrana Tamani, Gloria Marina (2023)
This research has been developed with the intention of determining the relationship between the Learning Strategies at Home and the learning of social personnel in four-year-old children of the Initial Educational Institution No. 454 "Mi Casita del Saber" Nauta, 2022. The research was of a relational type, with a field, correlational, and transactional design. The population was made up of all the parents and four-year-old children of the Initial Educational Institution No. 454 "Mi casita del saber" Nauta, 2022, totaling 45. The techniques have been the survey and observation and as instruments used were the questionnaire and the observation guide to obtain data previously validated by expert judgment, it is concluded that the correlation between both variables is low (rs= 0.044*; Sig. < 0.05). The research hypothesis is not met, the hypothesis "There is no significant relationship between the learning strategies at home and the learning of social personnel in four-year-old children of the Initial Educational Institution No. 454 "Mi casita del Know” Nauta – 2022